210-W, Quasi-Continuous Wave, Nd:YAG InnoSlab Laser at 1319 nm - Xiangrui Meng; Xingwang Luo; Junzhi Ye; Xiaoming Chen; Xuguang Zhang; Lei Zhang; Qingsong Gao; Baole Lu (Photonics, 2023)
In this paper, we demonstrate a high-power, quasi-continuous wave using a laser-diode dual-end-pumped Nd:YAG InnoSlab laser at 1319 nm. The maximum average output power of 210 W at a single 1319 nm wavelength is obtained with an optical-optical efficiency of 18.8% from absorbed pump power to laser output. The output pulse duration is 246 μs at the repetition of 500 Hz, and the beam quality factors of M2 are 1.37 and 1.47 in the horizontal and vertical directions, respectively. This is the first report on high-power, quasi-continuous wave using Nd:YAG InnoSlab lasers at 1319 nm with good beam quality.